Primitive Trees for Precomputed Distance Queries. (6th May 2013) - Lee, Sung‐Ho; Park, Taejung; Kim, Chang‐Hun
Abstract: We propose theprimitive tree, a novel and compact space‐partition method that samples and reconstructs a distance field with high accuracy, even for regions far from the surfaces. The primitive tree is based on the octree and stores the indices of the nearest primitives in its leaf nodes. Most previous approaches have involved a trade‐off between accuracy and speed in distance queries, but our method can improve both aspects simultaneously. In addition, our method can sample unsigned distance fields effectively, even for self‐intersecting and nonmanifold models. We present test results showing that our method can sample and represent large scenes, with more than ten million triangles, rapidly and accurately.